Synthesis, antiproliferative and antiplasmodial evaluation of new chloroquine and mefloquine-based harmiquins - Pavić Kristina; Poje Goran; Carvalho Lais Pessanha De; Held Jana; Rajić Zrinka (Acta Pharmaceutica)
Here we present the synthesis and evaluation of the biological activity of new hybrid compounds, ureido-type (UT) harmiquins, based on chloroquine (CQ) or mefloquine (MQ) scaffolds and β-carboline alkaloid harmine against cancer cell lines and Plasmodium falciparum. The hybrids were prepared from the corresponding amines by 1,1′-carbonyldiimidazole (CDI)-mediated synthesis. In vitro evaluation of the biological activity of the title compounds revealed two hit compounds. Testing of the antiproliferative activity of the new UT harmiquins, and previously prepared triazole-(TT) and amide-type (AT) CQ-based harmiquins, against a panel of human cell lines, revealed TT harmiquine 16 as the most promising compound, as it showed pronounced and selective activity against the tumor cell line HepG2 (IC50 = 5.48 ± 3.35 μmol L−1). Screening of the antiplasmodial activities of UT harmiquins against erythrocytic stages of the Plasmodium life cycle identified CQ-based UT harmiquine 12 as a novel antiplasmodial hit because it displayed low IC50 values in the submicromolar range against CQ-sensitive and resistant strains (IC50 0.06 ± 0.01, and 0.19 ± 0.02 μmol L−1, respectively), and exhibited high selectivity against Plasmodium, compared to mammalian cells (SI = 92).